The effectiveness of learning media on the outcome of computer and basic network of vocational students - Devega, Army Trilidia; Ambiyar, Ambiyar; Panyahuti, Panyahuti; Adi, Novi Hendri; Riyanda, Afif Rahman (Jurnal Pendidikan Teknologi Kejuruan, 2022)
Learning media is a tool that can help the teaching and learning process so that the meaning of the message conveyed becomes clearer and the goals of education or learning can be achieved effectively and efficiently. The results given to students in the form of an assessment after following the learning process with the value of knowledge, attitudes, skills in students with changes in behavior can also be called student learning outcomes. One source of student learning to obtain messages and information provided by the teacher so that learning materials can be further improved and form knowledge for students is using Learning Media. In this study, researchers used research and development (R&D) methods, and the ADDIE development model. This interactive learning media is designed using the Lectora application. The results of this study are the effectiveness of the media using time series results of student learning mastery increased by 20% effectively to improve student learning outcomes through tests. A score of 0.52 was obtained in the medium category.